Pembuatan dan Pengujian Pembangkit Listrik Tenaga Mikrohidro Turbin Banki Daya 200 Watt - Larasakti, Andi Ade; Himran, Syukri; Arifin, Andi Syamsul (Jurnal MEKANIKAL, 2012)
The study aims to find out how to get start in fabricating Banki turbine of 200 watt in electical power capacity and determine the influence of fixed blade opening and dynamometer loading variation. This study was performed and examined directly in the laboratory of University of Muslim Indonesia Makassar, turbine rotation velocity, water capacity, were measured using hand tachometer, and manometer respectively. The fixed blade valve setting also performed during the test.The result of study show that fixed blade opening with load variation at constant rotation turbine produced maximum power as follows: fixed blade opening of 12o with 2 kg load in 550 rpm produced 72 watt of electrical power and maximum fixed blade opening of 20o with 5.2 kg load in 550 rpm produced 186 watt of electrical power.